The Challenges Perceived in Teaching English with Audiobooks for Tenth-Grade, First-Semester Visually Impaired Students at SLB 1 Tabanan - Dewi, Sintha Karmila; Kusuma, I Putu Indra; Pratiwi, Ni Putu Astiti Pratiwi; Ana, I Ketut Trika Adi (Lexeme : Journal of Linguistics and Applied Linguistics, 2026)
The objective of the study was to explore the challenges perceived by English teachers and tenth grades first semester visual impaired students at SLB N 1 Tabanan regarding the potential use of audiobooks for learning English before their introduction. Employing a qualitative research design, the study adopted the Successive Approximation Model (SAM). Data were collected through classroom observation, interviews, and reflective journaling. Qualitative data from field notes and interview transcripts were analyzed using content analysis by Krippendorff (2004). The findings reveal that although audio-based media are commonly used, they are generic, minimally interactive, and inadequately adapted to students’ needs, resulting in reduced engagement, limited speaking confidence, and fluctuating motivation. Both teachers and students expressed positive perceptions of audiobooks, highlighting the need for clear narration, appropriate duration, bilingual explanations, and easy accessibility. Thus, the study confirms that well-designed audiobooks hold strong potential as an inclusive learning medium to enhance listening and speaking skills for visually impaired students and to bridge the gap between inclusive education theory and classroom practice. Teachers, learning designers, and other education stakeholders can use the implications of these findings to improve the efficacy, accessibility, and inclusivity of English language instruction for students with visual impairments.